Multigene analyses resolve early diverging lineages in the Rhodymeniophycidae (Florideophyceae, Rhodophyta). Issue 4 (27th June 2016) - Saunders, Gary W.; Filloramo, Gina; Dixon, Kyatt; Le Gall, Line; Maggs, Christine A.; Kraft, Gerald T.
Abstract : Multigene phylogenetic analyses were directed at resolving the earliest divergences in the red algal subclass Rhodymeniophycidae. The inclusion of key taxa (new to science and/or previously lacking molecular data), additional sequence data (SSU, LSU, EF2, rbc L, COI‐5P), and phylogenetic analyses removing the most variable sites (site stripping) have provided resolution for the first time at these deep nodes. The earliest diverging lineage within the subclass was the enigmatic Catenellopsis oligarthra from New Zealand (Catenellopsidaceae), which is here placed in the Catenellopsidales ord. nov. In our analyses, Atractophora hypnoides was not allied with the other included Bonnemaisoniales, but resolved as sister to the Peyssonneliales, and is here assigned to Atractophoraceae fam. nov. in the Atractophorales ord. nov. Inclusion of Acrothesaurum gemellifilum gen. et sp. nov. from Tasmania has greatly improved our understanding of the Acrosymphytales, to which we assign three families, the Acrosymphytaceae, Acrothesauraceae fam. nov. and Schimmelmanniaceae fam. nov.